DEVELOPMENT OF FUN THINKERS BOOK MEDIA ON THEMATIC LEARNING THE BEAUTY OF TOGETHERNESS THEME FOR FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Anis Kurnikmah; Tio Gusti Satria; Andri Valen (Universitas Trunojoyo Madura, 2022)
This study aims to develop a product in the form of a media fun thinkers book with the theme of the beauty of togetherness that is valid and practical for use in learning. The sample population used is the fourth grade students of SD Negeri Sidomulyo as many as 3 students for the one to one test and 6 students for the small group test. The type of research that the researcher uses is the development of the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The data collection technique used a validation questionnaire of linguists, media experts, material experts and practicality questionnaires for teachers and students. Based on the results of the analysis of the three experts, namely linguists, media experts and material experts, it shows that the fun thinkers book media in learning the theme of the beauty of togetherness meets the valid criteria with an average score of 88%. While the results of the analysis of the practicality of the teacher obtained a percentage of 86.15% and the analysis of the practicality of the students obtained 96.6% with a very practical category. So that the fun thinker book media meets the valid and practical criteria and can be used in the learning process.